(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
No language is relevant to society and cannot develop on its own outside of society. Language is, first of all, a means of interaction between society and people, so society is a direct link between people and the formation of language vocabulary. It is important to remember that language itself is important because of the laws of its internal system of formation. Depending on the situation, a single idea in any developed language will be interpreted differently. Regardless of style, stylistic color, or situation, there are neutral words that are used in communication only for certain situations as the core of the language.